2010
DOI: 10.2134/jeq2009.0298
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Polycyclic Aromatic Hydrocarbons and Their Oxygen‐Containing Derivatives and Metabolites in Soils

Abstract: Although polycyclic aromatic hydrocarbons (PAHs) have been extensively studied, the knowledge of their oxygen-containing derivatives and metabolites (OPAHs) in soils is limited. We modified and tested an existing analytical protocol involving pressurized liquid extraction of soil followed by fractionation of target compounds into PAHs and OPAHs on a silica gel column and gas chromatography/ mass spectrometry-based separation and quantification. Polycyclic aromatic hydrocarbons and carbonyl-OPAHs were quantifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
51
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(56 citation statements)
references
References 62 publications
4
51
1
Order By: Relevance
“…The calculated ratios of the sum of oxy-PAH-9/PAH-16 are 0.04, for 9-fluorenone/fluorene 0.2 and for 9,10-anthraquinone/anthracene 0.6. These ratios are much lower than reported from other sites contaminated by PAHs [16,34].…”
Section: Pahs and Oxy-pahs Contentcontrasting
confidence: 72%
“…The calculated ratios of the sum of oxy-PAH-9/PAH-16 are 0.04, for 9-fluorenone/fluorene 0.2 and for 9,10-anthraquinone/anthracene 0.6. These ratios are much lower than reported from other sites contaminated by PAHs [16,34].…”
Section: Pahs and Oxy-pahs Contentcontrasting
confidence: 72%
“…Dichloromethane was used as solvent for the first extraction, and a mixture of acetone: dichloromethane (2:1 v/v) was used for the second extraction. The instrument conditions of ASE were the same as specified elsewhere (Bandowe and Wilcke, 2010). The two extracts obtained from each sample were combined; 15 mL of hexane was added and concentrated to a volume <1 mL using a TurboVap II Concentrator Workstation (Biotage, Charlotte, NC, USA) operating at a water bath temperature of 35°C pressurized with N 2 gas at pressure of 15 Psi.…”
Section: Analyses Of Polycyclic Aromatic Compoundsmentioning
confidence: 99%
“…In addition, because they are more polar than the parent PAHs, oxyPAHs can exhibit greater mobility within a contaminated environmental system (2, 10). Little is known about the fate of oxyPAHs in contaminated systems, in part because relatively few studies have attempted to identify these compounds and the analytical methods have not yet been standardized (11,12).It is not possible to assess the source(s) or fate of oxy-PAHs in contaminated systems from observation of their presence alone, although it has been suggested that the ratio of an oxy-PAH to the parent PAH can be diagnostic of the source (3, 13). Oxy-PAHs can be present in the same source as the PAHs (2) (such as coal tars), formed in the atmosphere by heterogeneous reactions on particles containing PAHs (14) that can reach soil or sediment by deposition, or produced by chemical or photochemical oxidation of PAHs in situ (2).…”
mentioning
confidence: 99%
“…In addition, because they are more polar than the parent PAHs, oxyPAHs can exhibit greater mobility within a contaminated environmental system (2, 10). Little is known about the fate of oxyPAHs in contaminated systems, in part because relatively few studies have attempted to identify these compounds and the analytical methods have not yet been standardized (11,12).…”
mentioning
confidence: 99%